Dari Hukum ke Realitas: Penegakan Hukum terhadap Pekerja Seks Komersial dalam Kasus Prostitusi - Tiara Nurul Falaq; Johamran Pransisto; Muhammad Tahir (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2024)
This study aims to identify the legal rules that apply to Commercial Sex Workers (PSK) and explore the law enforcement measures against them, as well as the reasons behind the rise of prostitution. The method used is empirical normative legal research with case studies in the jurisdiction of the Parepare Police, using primary and secondary data. Data analysis was carried out qualitatively. The results of the study show that the act of prostitution in Parepare is influenced by several factors, including the damage to people's moral values, the spread of sexually transmitted diseases, sexual deviation, the mental decline of the perpetrators, the decline in religious knowledge, and easy access to social media related to prostitution. Law enforcement against prostitution violations is carried out based on community complaints and refers to Kitab Undang-Undang Hukum Pidana (KUHP) Pasal 296 and Pasal 506 and Undang-Undang Nomor 44 Tahun 2008 tentang Pornografi.